American ideals, and other essays, social and political - Roosevelt, Theodore, 1858-1919; Greene, F. V. (Francis Vinton), 1850-1921 (Salt Lake City, UT : Project Gutenberg, 2023)
"American Ideals and Other Essays, Social and Political" by Theodore Roosevelt is a collection of essays written in the late 19th century. This work explores various themes related to American identity, ideals, and practical politics, drawing from Roosevelt's extensive experiences in governance and reform. The essays address important concepts, including the responsibilities of American citizens, the challenges of corruption in politics, and the need for collective action toward achieving societal progress. The opening of the text provides a biographical sketch of Roosevelt, highlighting his diverse background and his rise through political ranks, from a young legislator to the Vice Presidency. It discusses his commitment to reforming government systems, emphasizing the necessity for active participation in public service and the importance of honesty and integrity in American politics. Roosevelt's strong belief in the potential for civic duty as a means to combat corruption and ensure good governance is conveyed through his call for citizens to engage not just as critics, but as proactive forces in shaping their nation$1 (Bs future. (This is an automatically generated summary.)s
American ideals -- True Americanism -- The manly virtues and practical politics -- The college graduate and public life -- Phases of state legislation -- Machine politics in New York City -- Six years of Civil Service reform -- Administering the New York Police Force -- The vice-presidency and the campaign of 1896 -- How not to help our poorer brother -- The Monroe doctrine -- Washington's forgotten maxim -- National life and character -- Social evolution -- The law of civilization and decay -- Reform through social work.
Release date is 2023-09-06
Emmanuel Ackerman and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: United States -- Politics and government; National characteristics, American; United States -- Social conditions -- 1865-1918